1991
DOI: 10.1179/mst.1991.7.7.613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of titanium on hot ductility of as cast steels

Abstract: The influence on hot ductility ofa small addition (0·02%) of titanium to C-Mn-Al-Nb steel and 0·05jO·15%C-Mn-AI steels has been examined over the temperature range 700-1100°C and at a strain rate of 5 x 10-3 S -1. The tensile samples used were tested after melting, solidifying, and cooling directly to test temperature. The y grain sizes at test temperature were coarse and were independent of titanium or carbon content. In niobium containing steel, little influence of titanium was observed when the cooling rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Cardoso et al [71] have also shown that an increase in the aluminum level in C-Mn-Al steel extends the ductility trough to higher temperatures and this is related to the aluminum nitride which has precipitated out, delaying the onset of dynamic recrystallisation. In this work the [Al] x [N] value is 4.25 x 10 -4 which is above the level quoted earlier [79]. AlN when it precipitates out of solution is particularly damaging to ductility and there is increasing evidence [122,123] that it can precipitate out from the melt as a very thin film, which covers the austenite grain surfaces.…”
Section: Aluminiumsupporting
confidence: 52%
See 4 more Smart Citations
“…Cardoso et al [71] have also shown that an increase in the aluminum level in C-Mn-Al steel extends the ductility trough to higher temperatures and this is related to the aluminum nitride which has precipitated out, delaying the onset of dynamic recrystallisation. In this work the [Al] x [N] value is 4.25 x 10 -4 which is above the level quoted earlier [79]. AlN when it precipitates out of solution is particularly damaging to ductility and there is increasing evidence [122,123] that it can precipitate out from the melt as a very thin film, which covers the austenite grain surfaces.…”
Section: Aluminiumsupporting
confidence: 52%
“…The greatest improvement in ductility that has been found so far on adding Ti to as-cast steel, is when slow cooling to the test temperature has been used [79]. Whereas cooling an Nb containing steel at 100 o C/min to the test temperature only gave a small improvement in 44 ductility when Ti was present, reducing the cooling rate to 25 o C/min resulted in a significant benefit, Fig.2.22.…”
Section: Fig221mentioning
confidence: 98%
See 3 more Smart Citations